Evaluation of effect of recasting of nickel-chromium alloy on its castability using different investment materials: An in vitro study - Abhinav Sharma; Shobha J Rodrigues; Thilak B Shetty; Vidya K Shenoy; Mahesh Mundathaje; Sharon Saldanha (Wolters Kluwer Medknow Publications, 2016)
Context: Castability has been found to be affected by many aspects of the entire casting system. Very few references in dental literature are available regarding recasting of the base metal alloys. Aims: To evaluate and compare the castability of fresh and reused nickel-chromium alloy and to evaluate the effect of two brands of investment materials on castability of nickel-chromium alloy. Subjects and Methods: For the experimental purpose of evaluation of the effect of recasting of nickel-chromium alloy on its castability, different percentages of new and casted alloy (Nickel-chromium alloy-(Wirolloy NB, Type 4 (Ni-67%; Cr-25%; Mo-5%; Si-1.5%; Mn, Nb, B, C each <1%) and two commercial brands of investment materials namely, Deguvest Impact (Degudent; Dentsply Germany) and Bellavest SH (Degudent; Dentsply Germany) was used to obtain 30 samples. Castability value was obtained using Whitlock's formula. Student t-test and one way ANOVA using SPSS 20.0 software was done. Results: The results of this study confirm earlier works that demonstrate that there is no significant difference in castability values of new and recast alloys. In addition, it also demonstrated, there was no difference in castability using Deguvest Impact and Bellavest SH investment materials. Conclusions: Within the limitations of the study, it was concluded that there was no significant difference found in castability of different percentage combinations of new and once casted alloy using two investment materials. The addition of new alloy during recasting to maintain the castability of nickel-chromium alloy may therefore not be required.